Ten Years after Sutton (2012): Quo Vadis Feedback Literacy? (A Bibliometric Study) - Imelda Gozali; Abdul Syahid; Nunung Suryati (UIN Salatiga, 2023)
Drawing on the construct of Academic Literacy, Paul Sutton coined the term